2013
DOI: 10.1590/s1516-35982013001000006
|View full text |Cite
|
Sign up to set email alerts
|

Digestible tryptophan requirements for broilers from 22 to 42 days old

Abstract: -The objective of this experiment was to establish different criteria to evaluate the requirements of digestible tryptophan for broilers from 22 to 42 d of age, using different regression models (quadratic, exponential and Linear Response Plateau) and in case of statistical significance the comparison of means by Duncan test at 5% probability was also adopted. A total of 1,920 Cobb 500 male broilers were distributed in a completely randomized experimental design, with 6 treatments (6 digestible tryptophan leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
2
8
0
1
Order By: Relevance
“…Similarly, no effect was noticed on carcass traits. These findings are supported by the previous studies (Duarte et al 2013;Mr & Azam, 2014) in which Trp supplementation had similar response. The similar result for feed intake (Rosebrough, 1996) reported that the feed intake was decreased when broiler chicken was fed by the diet containing low crude protein and excess level of Trp supplement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, no effect was noticed on carcass traits. These findings are supported by the previous studies (Duarte et al 2013;Mr & Azam, 2014) in which Trp supplementation had similar response. The similar result for feed intake (Rosebrough, 1996) reported that the feed intake was decreased when broiler chicken was fed by the diet containing low crude protein and excess level of Trp supplement.…”
Section: Discussionsupporting
confidence: 90%
“…The similar result for feed intake (Rosebrough, 1996) reported that the feed intake was decreased when broiler chicken was fed by the diet containing low crude protein and excess level of Trp supplement. Duarte et al (2013) also concluded that Trp had no effect on feed intake in broiler chicken. This result might be due to the crude protein (18.4%) in diet.…”
Section: Discussionmentioning
confidence: 99%
“…Also Corzo (2012) reported that Body weight gain, feed consumption, and feed conversion responses of Cobb 500 male broiler chicks fed increasing dietary ratios of Tryptophan: Lysine (19.5 and 19.7% %) from 0 to 18 d post hatch. ( Patil et al, 2013;Duarte, et al, 2013 andWong et al, 2014) who found that supplementation tryptophan level of broiler diet improvement in feed conversion ratio of birds. Emmanuel et al (2016) found that chicks fed 0.15% total dietary tryptophan had significantly higher (p<0.05) value for feed intake (1,789.90 g).…”
Section: Results Inmentioning
confidence: 99%
“…(Rosa and Pesti 2001, Fraiha 2002and Tabiri et al, 2002, reported that the level of 0.25% tryptophan supplementation is necessary to maximize feed intake. Duarte et al (2013) noted that the level of 0.23% of digestible tryptophan numerically improves feed conversion.…”
mentioning
confidence: 99%
“…Treatments consisted of a isoleucine-deficient basal diet, formulated with digestible amino acids, according to the ideal protein concept, or rather, from 22 to 42 days of age, supplemented with five different digestible isoleucine levels, using 0.7642% of digestible threonine, 0.1919% of digestible tryptophan and 0.8802 of digestible valine, following Duarte et al (2014); Duarte et al (2012); Duarte et al (2013), respectively.…”
Section: Animals and Experimental Proceduresmentioning
confidence: 99%